Application of plastic containers with RFID in the marketing of fruit and vegetables in Taiwan - Hung, Chih-Cheng; Sheng, Chung-Teh (International Journal of Agricultural and Biological Engineering, 2012)
Abstract: This study aims to present a set of operation and management systems for containers used in the transport of fresh agricultural produces. The proposed system utilizes Radio Frequency Identification (RFID) and technologies related to information engineering. An operation and information management system for the marketing of fruit and vegetables using RFID-embedded plastic containers is well planned and developed. In order to promote the use of plastic containers, the study designs an energy-saving and environmentally-friendly container that allows for standardized operation. A related standardized operation flow is tested to fully satisfy the wholesale market demands. The entire flow and operation is also tested by all related sectors of the system. With the application of the RFID tag, real time information generated at the production center can be sent to the wholesale market through a wireless network, thus reducing the labor needed for data input while also reducing human error at the market. This may improve tallying efficiency and reduce costs. Keywords: RFID, plastic container, informatization, fruit and vegetables, Taiwan DOI: 10.3965/j.ijabe.20120501.004 Citation: Chih-Cheng Hung, Chung-Teh Sheng. Application of plastic containers with RFID in the marketing of fruit and vegetables in Taiwan. Int J Agric & Biol Eng, 2012; 5(1): 35